Group IV Direct Band Gap Photonics: Methods, Challenges, and Opportunities - Geiger, Richard; Zabel, Thomas; Sigg, Hans (Frontiers in Materials, 2015)
The concept of direct band gap group IV materials offers a paradigm change for Si-photonics concerning the monolithic implementation of light emitters: The idea is to integrate fully compatible group IV materials with equally favorable optical properties as the chemically incompatible group III-V-based systems. The concept involves either mechanically applied strain on Ge or alloying of Ge with Sn and permits to drastically improve the insufficient radiative efficiency of Ge. The favorable optical properties result from a modified band structure transformed from an indirect to a direct one. The first demonstration of such a direct band gap laser, accomplished in GeSn, exemplifies the capability of this new concept. These systems may permit a qualitative as well as a quantitative expansion of Si-photonics into traditional but also new areas of applications, provided they can be operated energy efficiently, under ambient conditions and integrated with current Si technologies. This review aims to discuss the challenges along this path in terms of fabrication, characterization and fundamental understanding, and will elaborate on evoking opportunities of this new class of group IV-based laser materials.